Numerical simulations of binary mixtures under gravity deposition using the discrete element method - Jiang, Chao, author; Heyliger, Paul, advisor; Bareither, Christopher, committee member; Ellingwood, Bruce R., committee member; Venayagamoorthy, Karan, committee member; McGilvray, Kirk, committee member (Colorado State University. Libraries, 2021)
Binary granular mixtures are frequently used in manufacturing, geotechnical engineering, and construction. Applications for these materials include dams, roads, and railway embankments. The mixing process requires dealing with particles with varying sizes and properties, and the complex composite nature of these mixtures can bring unpredictable results in overall performance. At present, there are no specifications for mixing these materials that can be used to quantify the levels of mixing and give estimates of the overall bulk properties. In this study, the Discrete Element Method (DEM) is used to examine the mechanics of the mixing process and give guidelines on how to achieve a well-mixed aggregate. A comprehensive non-linear visco-elastic damping collision model was developed to better represent the interactions between two dissimilar particles. A general Hertz model was applied for describing the normal force but a refined non-linear spring model was generated to imitate the friction force behavior without having to consider the entire loading history. A transition zone revealing the interactions between static and dynamic friction forces was shown in our numerical results. A moment resistance model was also added to capture the behavior of particle surface asperities and the damping force was calculated using relative motion. An alternative condition was applied to determine the end of a collision. Excellent agreement was found with well-established benchmark solutions and new results are also provided for future comparisons. Using this new DEM model, the mixing process of binary unbonded particles was studied using the effects of the number and position of geometric mixing obstacles and the number of mixing iterations. It was found that the mixing degree can be best quantified by measuring the spatial variation of the volume ratio φv. It was also found that small adjustments in the geometric position of the mixing obstacles could have a significant impact on the final mixing parameters. Surprisingly, the results indicate that two mixing iterations provided almost identical levels of mixing regardless of the number and nature of mixing obstacles. Estimates of the bulk elastic constants were provided and showed a high level of anisotropy as measured by the Poisson ratios for the horizontal versus vertical planes of the control volume. Particle crushing is a typical characteristic of many granular materials and can influence the mixing process, and it is possible to model non-particulate materials by bonding individual spheres together. The particle interactions and possibly impact with mixing barriers can result in the fracture of these solids as the allowable bond strength is exceeded. Therefore, the strength of the bond between individual particles that can be part of the mixing process is a critical parameter. The parallel bond model of Potyondy and Cundall (2004) was extended with the present DEM model was used to study the effects of bond strength on the mixing and mechanical properties of binary mixtures. Three types of particle blocks were studied for this purpose: unbonded, weakly bonded, and strongly bonded particles. The bonded particles result in a wider range of reflection angles as the particles interact with geometric mixers and simultaneously change and improve the level of mixing. Overall, these simulations serve to established specific guidelines and provide a basis for field-level mixing operations. They also provide some levels of expectation for the final mixing and bulk elastic behavior for the final aggregates.